FACTORS INFLUENCING VISITS TO HALAL RESTAURANTS HOTELS IN LOMBOK, NTB - Rosida Rusmiati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
This study is motivated by the scarcity of research examining the consumers of halal-certified hotel restaurants. Lombok Island is the best halal tourism destination in Indonesia, making research on the island particularly intriguing. The objective of this study is to empirically investigate the influence of personal factors, religiosity, and social perception on the decision to visit halal-certified hotel restaurants on Lombok Island. This research employs multiple regression analysis with a sample size of 154 respondents, using a convenience sampling technique. The measurement scale utilized is a Likert scale (1-5), ranging from strongly disagree to strongly agree. The findings indicate that personal factors, religiosity, and social perception have a positive and significant effect on the decision to visit halal-certified hotel restaurants on Lombok Island. This study is limited by a small sample size; therefore, we recommend further research with a larger number of respondents and a more diverse range of regions.